The accommodation of minority nationalism in multination states: An appraisal of scotland and devolution - (:unkn) unknown (My University, 2010)
Kurulduğundan bu yana, Avrupa ulus-devleti her zaman isteklerine karşı sık sık birleşmiş önemli azınlıkları bünyesinde bulundurmuştur. Tartışmalı bir şekilde, 1707 yılında İngiltere ile olan birleşme, İskoçların daha geniş ve gelişmiş bir alandan yararlanmalarına olanak sağlamıştır. Ancak yirminci yüzyılın küreselleşmiş dünyasında, İngiliz devletinin “görkemli ve huzurlu” cazibesi zayıflamıştır ve bu, çok güçlü yapısal değişimlere yol açmıştır. 1997 yılında İşçi Partisi’nin iktidara gelmesinin ardından İskoçya, kanun çıkarma ve bütçe kontrolü gibi devredilmiş güçlerin bulunduğu bir meclis elde etmiştir. Makale, İskoçların görmek istediği yapısal koşullarda gerilemenin en üst düzeyde olduğunu ve düzeltilmesi gerekmesine rağmen, gerilemenin gerçekleşmesinin, ayrılıkçılığa ışık tutmadığını veya Birleşik Krallığın şu anki bölgesel bütünlüğünü tehlike altına sokmadığını tartışmaktadır.

Once it was created, the European nation-state invariably contained significant minorities often incorporated against their will. Arguably, the 1707 Union with England allowed the Scottish people as a whole to benefit from membership of a larger developed area. In the late twentieth century globalised world, though, the ‘imperial and welfare’ appeal of the British state started to weaken, leading to strong demands for constitutional change. Following the election of a Labour government in 1997 Scotland gained a Parliament with devolved powers which included the right to enact laws and control a budget. The article argues that devolution appears to be the upper limit of what many Scottish people wish to see in constitutional terms and that the implementation of devolution, while requiring improvements, does not seem to serve as a staging post for secessionism or currently endanger the territorial integrity of the United Kingdom.